Statement...at the Farewell and Awards Dinner of the CAIC Seventh Annual Private Sector Conference - Carrington, Edwin W. ([CCS] [Georgetown]GY, 1995)
Looks at the role of the private sector in the Caribbean Region. Acknowledges the contribution made by Mr Patterson Thompson in the development of the private sector of the Region.